2020
DOI: 10.1111/ppc.12646
|View full text |Cite
|
Sign up to set email alerts
|

Health anxiety during the early phases of COVID‐19 pandemic in Turkey and its relationship with postpandemic attitudes, hopelessness, and psychological resilience

Abstract: Purpose: To investigate health anxiety-related factors in the early stages of pandemic in Turkey. Design and Methods: This study included 1046 participants who responded to the online survey anonymously between 28 March and 04 April 2020. Findings: Demographic data, postpandemic attitudes towards the elderly and precaution-taking behaviors were health anxiety-related factors. The main predictors of the health anxiety were the level of hopelessness, perception of self, time spent on social media, and following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
3
13
0
1
Order By: Relevance
“…The models of these interventions are beyond the scope of this study, however, it is worth remembering that—as shown by several reports—excessive exposure to information from various media sources increases the intensity of anxiety [ 53 , 54 , 55 ]. It has also been proven that focusing on the disease caused by the SARS-CoV-2 virus is the greatest risk of increasing the severity of anxiety [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The models of these interventions are beyond the scope of this study, however, it is worth remembering that—as shown by several reports—excessive exposure to information from various media sources increases the intensity of anxiety [ 53 , 54 , 55 ]. It has also been proven that focusing on the disease caused by the SARS-CoV-2 virus is the greatest risk of increasing the severity of anxiety [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hacimusalar et al explored the level of anxiety and hopelessness in the groups with and without HWs ( n = 1121: HWs, 52%) and found a higher level of hopelessness and anxiety in the group with HWs and a positive relationship between hopelessness and anxiety and argued that anxiety and uncertainty can exacerbate the level of hopelessness (Hacimusalar et al, 2020). The literature has citations that hopelessness is associated with reduced physical function and lower physical activity in people with heart disease (Botterman, 2021), HWs with a high level of hopelessness attribute less meaning to life, which aggravates depression (Güngör & Uçman, 2020), there is a positive significant relationship between health anxiety and hopelessness seen in the early stages of the COVID-19 pandemic (r = 0.35, p < 0.01) (Kazan Kızılkurt et al, 2021), hopelessness is negatively correlated with life satisfaction (Kliem et al, 2018), and a negative predictor of resilience to stressful events (Saricali et al, 2020). In this study, as the state anxiety levels of HWs increased, the quality of life in the physical, psychological, and environmental health areas increased; however, as the hopelessness increased, the quality of life in the physical, psychological, social well-being, and environmental health areas decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The Personal and Occupational Information Form, the Turkish Version of the Shorter Version of the World Health Organization Quality of Life Instrument (WHOQOL-BREF-TR), the State-Trait Anxiety Inventory, and the Beck Hopelessness Scale (BHS) were used as data collection tools. It is noteworthy that the data collection tools we used in our study are also frequently used measurement tools in the literature for anxiety (Hacimusalar et al, 2020; Sakaoğlu et al, 2020), hopelessness (Franza et al, 2020; Güngör & Uçman, 2020; Kazan Kızılkurt et al, 2021; Kurian & Nishad, 2020; Saricali et al, 2020) caused by COVID-19, and the effects of COVID-19 on the quality of life of HWs (Sharma et al, 2021; Vitorino et al, 2021; Woon et al, 2021). In the study, after the questionnaire was created with Google Forms, they were sent to HWs by the researchers via social media sites (Instagram, Facebook, and WhatsApp).…”
Section: Methodsmentioning
confidence: 99%
“…In conclusion, Turkey is going through a rough time as the rest of the world and is not an exception in terms of increased symptoms of anxiety, depression, post-traumatic stress disorder and stress during the COVID-19 pandemic in the general population (Ustun, 2020 [6]); (Kazan Kizilkurt, Yilmaz, Noyan, & Dilbaz, 2020 [7]); (Xiong et al, 2020 [8]). Nevertheless this age-selected curfew and isolating them from the society, without any compensation mechanisms, might have severe future implications on the psychosocial development, education and psychological wellbeing of adolescents in addition to increased cognitive and physical impairments of elderly that has to be monitored in years to come.…”
Section: Short Lettermentioning
confidence: 99%